Studi Struktur Komunitas Fitoplankton Di Danau Batur, Kecamatan Kintamani, Kabupaten Bangli, Provinsi Bali - Komang Gustika Nirasari; I Wayan Arya; Sang Ayu Made Putri Suryani (GEMA AGRO, 2018)
Lake Batur is the largest lake in Bali with many activities surrounding that will have great impact on fertility of the lake. One key factor in the fertility of the lake is phytoplankton. Abundance of phytoplankton in the waters affected by several environmental parameters. This research was conducted at Lake Batur, Kintamani district, Bangli Regency, in February 2014. Study is to measure the composition, abundance, diversity, uniformity and dominance of phytoplankton in the waters, measuring parameters and aquatic physical chemistry. The diversity of phytoplankton species found in Lake Batur are 5 class consists of 20 genera. Phytoplankton abundance ranged from 232370-336325 ind/l are eutrophic lake. Phytoplankton diversity index were included in diversity, uniformity index is included in the low uniformity, dominance index showed no dominance. Physical and chemical parameters of water still shows a good value so that the waters of Lake Batur contamination has not occurred.